2002
DOI: 10.1385/endo:18:2:161
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Endocrinology in Hatano High- and Low-Avoidance Rats During the Estrous Cycle

Abstract: The high- and low-avoidance animals (HAA and LAA rats) were originally selected from Sprague-Dawley rats for their shuttle-box task. Reproductive endocrinology during the estrous cycle was compared between HAA and LAA rats. All HAA rats showed a regular 4-d estrous cycle, whereas most LAA rats (70.8%) showed a regular 5-d estrous cycle. The peak level of preovulatory luteinizing hormone (LH) surge level was significantly lower in LAA rats than in HAA rats on the day of proestrus. In contrast, the peak level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…The number of oocytes shed at first ovulation in HAAs was significantly larger than that of LAAs. A similar difference was also observed between adult cyclic HAAs and LAAs (Asai et al 2002). Thus, HAAs ovulate more oocytes than LAAs from the first estrus.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The number of oocytes shed at first ovulation in HAAs was significantly larger than that of LAAs. A similar difference was also observed between adult cyclic HAAs and LAAs (Asai et al 2002). Thus, HAAs ovulate more oocytes than LAAs from the first estrus.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, HAAs ovulate more oocytes than LAAs from the first estrus. Size-fractionated comparisons of ovarian follicles between adult HAAs and LAAs revealed that a greater number of large antral follicles had developed in HAA ovaries by noon of the day of proestrus as compared with LAAs (Asai et al 2002). In contrast, no differences in the numbers of oocytes shed at the induced ovulation were found between immature HAAs and LAAs, and the number in LAAs was comparable to that counted at the first ovulation.…”
Section: Discussionmentioning
confidence: 82%
“…Milk yield was significantly lower in LAA rats than in HAA rats. Our previous report showed LAA pups with reduced weight gain compared with HAA pups (Ohta et al 1998), LAA dams with a lowered prolactin secretion 15 min after suckling compared with HAA rats, and LAA dams with a lowered milk yield during a 15-min period of suckling compared with HAA dams (Ohta et al 2002). We also reported that there were no strain differences in the levels of milk ejection following oxytocin injection between HAA and LAA rats (Ohta et al 2002).…”
Section: Discussionmentioning
confidence: 47%
“…Adrenal weights are heavier in HAA rats than in LAA rats, and plasma concentrations of ACTH are higher in HAA rats than in LAA rats (Ohta et al 1999). HAA rats and LAA rats show differences in follicular development, luteal function and pattern of hormonal secretion during the oestrous cycle (Asai et al 2002). The body weights of the HAA pups are heavier than the LAA pups during the latter half of lactation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation